2019
DOI: 10.1186/s13046-019-1328-3
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1-mediated autophagy regulates sodium/iodide symporter protein degradation in thyroid cancer cells

Abstract: Background Sodium/iodide symporter (NIS)-mediated iodide uptake plays an important physiological role in regulating thyroid gland function, as well as in diagnosing and treating Graves’ disease and thyroid cancer. High-mobility group box 1 (HMGB1), a highly conserved nuclear protein, is a positive regulator of autophagy conferring resistance to chemotherapy, radiotherapy and immunotherapy in cancer cells. Here the authors intended to identify the role of HMGB1 in Hank’s balanced salt solution (HBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…Furthermore, the use of z-VAD-FMK, z-LEHD-FMK and z-IETD-FMK supports the involvement of caspase-cascades in SNG-mediated apoptosis in PTC cells. Autophagy is another important cellular degradation event associated with cell death, which has been shown to play an important role in cancer pathogenesis and therapy [62][63][64]. We found that SNG induces autophagy in PTC cells, as we detected increased expression of LC3, which is an important autophagic marker; this is in agreement with findings from a previous investigation [65].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the use of z-VAD-FMK, z-LEHD-FMK and z-IETD-FMK supports the involvement of caspase-cascades in SNG-mediated apoptosis in PTC cells. Autophagy is another important cellular degradation event associated with cell death, which has been shown to play an important role in cancer pathogenesis and therapy [62][63][64]. We found that SNG induces autophagy in PTC cells, as we detected increased expression of LC3, which is an important autophagic marker; this is in agreement with findings from a previous investigation [65].…”
Section: Discussionsupporting
confidence: 92%
“…Beyond cellular trafficking, the tumor microenvironment may affect protein degradation. Recent evidence demonstrates that autophagy is associated with NIS expression at the plasma membrane in thyroid cancers [80] and that HMGB1-mediated autophagy could regulate NIS protein degradation [81] . Considering the cross talk between hypoxia and autophagy mediated by HIFα and NF-κB [82] , our results suggest that such a mechanism could also be involved in reducing NIS-expression at the plasma membrane in cells under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that breast CSCs actively secrete HMGB1, which fosters their own self-renewal through the activation of the TLR2 signaling pathway in an autocrine or paracrine manner [ 73 ] ( Figure 3 ). Similarly, other groups demonstrated that cancer cells of different origin, such as those from malignant mesothelioma [ 85 ], breast [ 86 ], thyroid [ 87 ], and gastric [ 88 ] cancers, actively release HMGB1, which promotes their growth.…”
Section: Effect Of Chemo and Radiotherapy On Tlr2 Activationmentioning
confidence: 99%